PENGARUH KOMITMEN ORGANISASI, MOTIVASI DAN PEMBERIAN INSENTIF TERHADAP DISIPLIN KERJA GURU SMA N KABUPATEN KAMPAR - Fitriani Fitriani (UIR PRESS, 2015)
This study aims to determine the effect of organizational commitment, motivation, and incentives on teachers work discipline State High Schools Distric Kampar. The study used a quantitative approach with a causal-comparative method. The populations of this study were all teachers of the State High Schools Distric Kampar, they were all 796 teachers. The sample of this study were 172 teachers, taken from 13 schools. The sampling technique used was simple random sampling technique. Data collection technique used the Likert scale questionnaires. The data were analyzed using a descriptive analysis, simple regression analysis, and multiple regression analysis. The results of this study show that: (1) Organizational commitment has effect on the work discipline of teachers of the State High Schools Distric Kampar. Correlation values ​​obtained are 0.451 (p<0.05). Organizational commitment contributes 19.8%. (2) Motivation has effect on the work discipline of teachers of the State High Schools Distric Kampar. Correlation values ​​obtained are 0.440 (p<0.05). Motivation contributes 18.9%. (3) Incentives has effect on the work discipline of teachers of the State High Schools Distric Kampar. Correlation values ​​obtained are 0.374 (p<0.05). Incentives contributes 13.5%. (4) Organizational commitment, motivation, and incentives simultaneously affect the work discipline of teachers of the State High Schools Distric Kampar. Correlation values ​​obtained are 0.549 (p<0.05), and together contributes 28.9% of the work discipline of teachers of the State High Schools District Kampar.